Oral food challenge using different target doses and time intervals between doses. Issue 3 (June 2018) - Yanagida, Noriyuki; Sato, Sakura; Nagakura, Ken-ichi; Asaumi, Tomoyuki; Ebisawa, Motohiro
Abstract : Purpose of review: The oral food challenge (OFC) is a specific and vital tool used in clinical practice to identify the level of tolerance a person exhibits toward certain foods while diagnosing food-related allergies. OFC methods differ among countries. The aim of this review is to evaluate different target doses and determine the time interval between doses used for OFC. Recent findings: We analyzed recent articles on target doses and time between doses, and noted that some papers reported low target doses and less time between doses. A low-dose OFC appears to be a useful strategy; a time interval of 15 min between doses is short and that of at least 1 h is appropriate. Summary: Low-dose OFCs appear to be well tolerated and effective to avoid complete elimination of the consumption of foods causing allergies. For the safety of the OFC method, the time interval between doses should be more than 30 min.